2015
DOI: 10.5367/te.2014.0392
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Analysing Tourism Demand in Tourist Districts — The Case of Sicily

Abstract: This paper analyses tourism demand in the tourist districts in Sicily to study the relationship between the characteristics of tourists, types of tourism and expenditure. The data were obtained from a survey of tourists leaving the island after a holiday. The likelihood of choosing a type of holiday is estimated by means of a multinomial logistic model. The findings highlight the importance of the seaside, cultural, and food and wine/nature segments. The analysis of the distribution of per capita per day expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Comparing that research with the current study, certain differences can be identified. First of all, the current paper analyzes the likelihood of tourists visiting 11 attractions, whereas Asero and Tomaselli () analyzed the likelihood to choose a specific type of holiday. Moreover, the dataset used in the current research is much larger than the one used by Asero and Tomaselli ().…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing that research with the current study, certain differences can be identified. First of all, the current paper analyzes the likelihood of tourists visiting 11 attractions, whereas Asero and Tomaselli () analyzed the likelihood to choose a specific type of holiday. Moreover, the dataset used in the current research is much larger than the one used by Asero and Tomaselli ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous research carried out by Asero and Tomaselli (), a multinomial logistic model was used to study the effect of a set of variables in choosing three different types of holidays. Comparing that research with the current study, certain differences can be identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of discrete choice models, they cannot indicate to what extent the variables analyzed determine the behavior studied when data contain non-binary variables [57][58][59][60]. Nevertheless, several studies, such as the ones carried out by Masiero and Zoltan [61]; Li, Yang, Shen, and Wu [62]; and Asero and Tomaselli [63], used this technique to study the variables explaining why tourists chose to visit certain places. However, they do not identify to what extent the behavior is explained by the variables analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to (International Organisation of Vine and Wine, 2019), vineyard surface area was around 7,429 thousand ha (continued reduction), production was around 292,300 (an increase) and wine consumption was around 246,000 (an increase), unit 1000 hl (forecasted data) in 2018 (pp. [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to International Organisation of Vine and Wine (2019), a) the countries with the largest vineyard surface space are Spain, China, France, Italy and Turkey; b) the countries as the biggest wine producers are Italy, France, Spain, the USA and Argentina; c) the countries with the largest wine consumption (consummation) are the USA, France, Italy, Germany and China (pp. [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%